Alteration of Biodiesel Properties and Automotive Diesel Engine Performance due to Temperature Variation of the Transesterification Process - Widjanarko, Dwi; Kusumaningtyas, Ratna Dewi; Fathoni, Ahmad Afwan (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2020)
This study aimed to examine the effects of transesterification reaction temperature on the biodiesel properties and diesel engine performance. Biodiesel properties evaluated in this work included viscosity, density, and methyl ester content. Meanwhile, the diesel engine performance testing comprised the examination of the engines torque and power. The research was conducted in several stages, viz. producing biodiesel from fresh cooking oil with variations in transesterification temperature of 45, 55, and 65; testing the characteristics of biodiesel produced; blending biodiesel with petroleum diesel to result in B30 biodiesel fuel; and testing biodiesel fuel (B30) in diesel-engined vehicles. It was revealed that the higher transesterification temperature led to the lower biodiesel viscosity, the decreasing value of biodiesel density values, and the higher methyl ester content. Furthermore, it was also demonstrated that increase of the transesterification temperature resulted in the higher value of torque and power generated. However, compared to the petroleum diesel fuel (B0), biodiesel fuel (B30) exhibited the lower values of the engines torque and power. The highest average values of torque and power of B30 fueled diesel-engine were 108.11 Nm and 43.51 kW, respectively, provided by the biodiesel produced at the transesterification reaction temperature of 65.of 65.